Axisymmetric acoustophoresis for paper pulp concentration - Romain Le Magueresse (Elsevier, 2021)
In pulp and paper mills, mechanical processes such as screening and washing are commonly used to remove accumulated solid suspensions and concentrate the pulp. For environmental reasons and to optimize paper production, an emerging challenge is to develop alternative methods to concentrate paper pulp between 3 % and 6 % consistency for which the mixed pulp-water flow is complex. Among the proposed solutions in the literature, solutions based on acoustic levitation, also referred as acoustophoresis, of low-consistency pulp have been demonstrated as a potential solution for efficient pulp concentration and water recirculation. However, no sensitivity analysis on the ultrasound and physical parameters was proposed, limiting the extension to a realistic application. Thus, this paper presents a numerical modeling of acoustophoresis for pulp flow concentration in a pipe. For this purpose, the pulp flow is defined as a pseudo-homogenous fluid with a turbulent Low Re k- ∊ formalism, and the pulp particles are considered spherical and deflected by two acoustic forces, namely the acoustic radiation force and the Stokes drag force, both induced by an ultrasound wave generated along the walls of a circular pipe. The combined action of these two forces in the pulp flow enables to concentrate the particles at the center of the pipe. The influences of particle size and mechanical properties, fluid properties and ultrasound parameters are analyzed within a parametric study to optimize the particle deflection and the pulp concentration. The experimental feasibility of the industrial use of acoustophoresis for the concentration of paper pulp is demonstrated with a concentration gain up to 15 %.